PENGARUH KECERDASAN EMOSIONAL TERHADAP SIFAT-SIFAT KEPEMIMPINAN PADA MAHASISWA AKUNTANSI - Heriningsih, Sucahyo (Universitas Muhammadiyah Magelang, 2009)
This study aims to investigate the influence of intelegencia emotional components for selt communication, self control, motivation, empaty, social skill of leadership traits to accounting students. Population is accountantstudent to 1995 arms who has succeeded on finishing 120 SKS in Yogyakarta university for UPN, YKPN, UII. The sample was finished student using the method of research non probability sampling for purposive Sampling and Convinience Sampling. Regression analysis is used in testing the data in this study linier. Hypothetital test result show the significancy influence of intelegencia emotional components for leadership traits (hypothesis 1), althought 2-7 hypothesis to determine leadership traits is not significant.